An Optimized High-Order Implicit FDTD Solver with One-Sided TF/SF for Simulation of Photonic Devices - Abdallah, Hossam A (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper an optimized high-order implicit finite difference time domain (FDTD) solver with one-sided total-field/scattered-field (TF/SF) excitation is developed for numerical simulation of integrated optical components. The optimized FDTD algorithm reduces the number of operations and the storage requirements to perform the matrix inversion using LU decomposition. It is shown that the one-sided TF/SF formulation is more accurate in launching the exact power into the simulation domain as well as decreasing the load on the PML-ABCs. The implementation of this tool was done in the Prometheus program, a software package of Kymata Netherlands.